Jordanian Undergraduates’ Youths Use of the Dubbed Turkish Series and the Acquired Gratifications – A Survey Study on Public Universities’ Students - Jordan – - Abu Ewaidah, Hazem Khaled (Journal of Humanities & Social Sciences, 2020)
This study aimed to examine the patterns of Jordanian undergraduates’ youths exposure to the dubbed Turkish series, and to determine the motives and gratifications achieved by such series from their viewpoint, as well as to know the impact of these series and the values ​​it carries within on youth, by conducting a survey study using the questionnaire tool on a single stratified sample of (480) undergraduate Jordanian students. The study found that (48.3%) of the respondents watched the dubbed Turkish series for several reasons, most notably; achieving fun and entertainment and escaping from the pressures of their studies, most of the respondents believe that most values ​​included in the dubbed Turkish series contain threatening values ​​for morals and behavior, nonetheless, they provide an atmosphere of entertainment during their leisure time, and the most values ​​included in the dubbed Turkish series from the respondents’ point of view stated as they: "containing values ​​threatening to morals and behavior", and they "add an atmosphere of entertainment during my free time", while the most achieved gratifications achieved while watching these series are acquiring knowledge of the Turkish society, and for fun and entertainment inquiry. Among the most important recommendations recommended by the study, the need for intellectual supervision and control over the dubbed Turkish series, as they contain ideas that contradict our Arab and Islamic reality, for viewers in general and for young people in particular, and the need to commit drama presented through Arab screens to display everything that works to protect identity, privacy and values Cultural through highlighting the richness of Arab society with important customs and traditions.